PHYTOTHERAPY AS AN INTERVENTION IN WOMEN'S HEALTH: AN INTEGRATIVE LITERATURE REVIEW - Maria Charlianne de Lima Pereira Silva; Juan Carlos Alvarado Alcócer; Leilane Barbosa de Sousa; Edmara Chaves Costa; Olienaide Ribeiro de Oliveira Pinto; Nathanael de Souza Maciel; Francisco Jardsom Moura Luzia (Universidade Federal do Paraná, 2020)
Objective: to review the scientific publications available in the literature that describe phytotherapy as intervention in women's health. Method: an integrative literature review conducted in the MEDLINE, CINAHL, Scopus, and PUBMED databases. The following guiding question was adopted: "What evidence available in the literature describes the use of phytotherapy as intervention in women's health?" The descriptors used were the following: "Phytotherapy"; "Complementary Therapies"; "Women's Health". The process of surveying and gathering data took place in November and December 2018, in the city of Redenção, state of Ceará, Brazil. Results: nine articles were analyzed, three of which discussed medicinal plants used to treat menopause, three infertility, one gynecological infections, and two hormonal disorders. Conclusion: scientific studies on medicinal plants are still scarce, and the need for further studies and research on phytotherapy used in the treatment of gynecological diseases is essential.